How optional should regional anatomy be in a medical course? An opinion piece - Moxham, Bernard J.; Pais, Diogo (Clinical anatomy (New York, N.Y.), 2016)
The use of optional (elective) courses within the medical curriculum is increasingly being seen as a way of allowing students to pursue their studies according to their personal interests. For anatomy, particularly where the subject is being taught in an integrative curriculum and by means of a systemic approach, the development of elective regional anatomy courses is being employed to reintroduce regional anatomy and/or dissection by students. However, there is presently little evidence that objectively evaluates optional/elective courses. In this paper we critique the concept and practice of using elective courses and assess whether their deployment is ultimately in the interests of medical education, the medical profession, society in general and the layperson (potential patient) in particular. Clin. Anat. 29:702–710, 2016. © 2016 Wiley Periodicals, Inc.